Some Recursive Definitions for Linear Values of Cooperative TU Games. (24th February 2014) - Dragan, Irinel
Abstract : We give recursive definitions for the Banzhaf Value and the Semivalues of cooperative TU games. These definitions were suggested by the concept of potential for the Shapley Value due to Hart and Mas-Colell and by some results of the author who introduced the potentials of these values and the Power Game of a given game.